ANALYSIS OF THE REGULATION OF THE NATIONAL POLICE CHIEF IN LAW ENFORCEMENT OF BRAWL CASES IN CIREBON CITY - Dadan Taufik Fathurohman; Jeshline Efellien Wirawan; Orli Zafirah; Rida Putri Subrata; Zidane Fairuz Drajat (Ann Publisher, 2025)
Abstract Background. Fights between students are a form of collective violence that not only endangers the safety of the individuals involved but also has a detrimental effect on public order, comfort in the environment, and the education sector's reputation. This situation has transformed into one of the security and public order challenges that continues to emerge, including in the Cirebon City area. Aims. This study discusses the implementation of Regulation of the Chief of the National Police of the Republic of Indonesia Number 16 of 2006 concerning Guidelines for Mass Control in law enforcement against brawl cases in Cirebon City. Brawls, as a form of collective violence that often involves students and youth groups, are a serious challenge to maintaining public order. Methods. Through a normative juridical approach, this study analyzes the extent to which the police force carries out the regulation's mandate, especially in early detection, a persuasive approach, and applying human rights principles. Result. The study's results show a gap between legal norms in regulations and implementation in the field. The handling tends to be more repressive and lacks cross-sector coordination and community participation. Conclusion. Therefore, the supervision system needs to be improved, the role of Polmas optimized, and the apparatus's capacity increased in a humanistic and preventive approach. This research also highlights the importance of accountable evaluation after handling social conflicts to achieve legal effectiveness. Implementation. The success of law enforcement in brawl cases is determined by the authorities' ability to handle events technically and legally and build strong social relations with the community, especially the younger generation.